Chemical Screening Identifies EUrd as a Novel Inhibitor Against Temozolomide‐Resistant Glioblastoma‐Initiating Cells. (17th May 2016) - Tsukamoto, Yoshihiro; Ohtsu, Naoki; Echizenya, Smile; Otsuguro, Satoko; Ogura, Ryosuke; Natsumeda, Manabu; Isogawa, Mizuho; Aoki, Hiroshi; Ichikawa, Satoshi; Sakaitani, Masahiro; Matsuda, Akira; Maenaka, Katsumi; et al.
Abstract: Glioblastoma (GBM), one of the most malignant human cancers, frequently recurs despite multimodal treatment with surgery and chemo/radiotherapies. GBM‐initiating cells (GICs) are the likely cell‐of‐origin in recurrences, as they proliferate indefinitely, form tumors in vivo, and are resistant to chemo/radiotherapies. It is therefore crucial to find chemicals that specifically kill GICs. We established temozolomide (the standard medicine for GBM)‐resistant GICs (GICRs) and used the cells for chemical screening. Here, we identified 1‐(3‐C‐ethynyl‐β‐d ‐ribopentofuranosyl) uracil (EUrd) as a selective drug for targeting GICRs. EUrd induced the death in GICRs more effectively than their parental GICs, while it was less toxic to normal neural stem cells. We demonstrate that the cytotoxic effect of EUrd on GICRs partly depended on the increased expression of uridine‐cytidine kinase‐like 1 (UCKL1) and the decreased one of 5′‐nucleotidase cytosolic III (NT5C3), which regulate uridine‐monophosphate synthesis positively and negatively respectively. Together, these findings suggest that EUrd can be used as a new therapeutic drug for GBM with the expression of surrogate markers UCKL1 and NT5C3. Stem Cells 2016;34:2016–2025